Improved Design of Sleeve Coupling based on TRIZ Theory - Li Zhengfeng; Du Chunkuan; Wang Xinqin (Jixie chuandong)
In order to solve the inconvenience caused by the connected axial movement for disassembly of sleeve coupling,the technology conflicts are analyzed by using the theory of TRIZ,and then the conflicts matrix form is constructed. An improved design of sleeve coupling is carried out by employing the principles of segment,local conditions and prior action as well. The reasonable parameters are given by means of strength calculation,and the rationality of structure design is verified by finite element analysis. The new sleeve coupling is featured with accurate location,reliable connection and simple structure,which is hoped to expand its application.